Effect of pulse thermal treatments on the Ni(Ti)–n-21R(6H)-SiC contact parameters - Avdeev, S.P.; Agueev, O.A.; Konakova, R.V.; Kudryk, Ya.Ya.; Lytvyn, O.S.; Lytvyn, P.M.; Milenin, V.V.; Sechenov, D.A.; Svetlichny, A.M.; Soloviev, S.I.; Sudarshan, T.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
We present experimental investigations of the effect of rapid thermal treatment with incoherent IR radiation, as well as electric-spark and electron-beam treatments, on the electric parameters of Ni(Ti) n-21R(6H)-SiC contacts. The results obtained show that pulse thermal treatment is an efficient technique for local change of parameters of heterogeneous metal/silicon carbide structures.